(untitled) (Journal of The Colloquium for Information Systems Security Education, 2022)
This work presents LUCID Network Monitoring and Visualization Application (LNMVA), a comprehensive visualization software application for cyber security visualization. The application consists of five component types: components for monitoring network traffic, components for reporting various network messages, data storage components plus a visualization component and an automated animation reporting component. LNMVA can serve as an aid in teaching complex concepts in cybersecurity or to visually demonstrate active security events on a network to an audience or participants in the classroom or cyber defense competitions at near real-time speed. Its flexibility enables it to visualize different kinds of cybersecurity concepts, protocols and ideas. LNMVA is a sub-system of LUCID, a visualization and broadcasting system that aims to improve understanding and sense-making to participants or an audience. The system is targeted to intermediary or expert users engaged in cyber security exercises. Preliminary results from subject testing show that LNMVA with embodied virtual commentator provided an engaging environment to improve participants’ understanding and sense-making in active security events.